1997
DOI: 10.1007/bf02070704
|View full text |Cite
|
Sign up to set email alerts
|

Suppository administration of chemotherapeutic drugs with concomitant radiation for rectal cancer

Abstract: 5-Fluorouracil and mitomycin C suppository delivery combined with radiation causes less systemic toxicity and is more effective than intravenous administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“… 12 , 13 Numerous studies have shown that the colon suppository administration of 5FU appeared to be efficient and showed pharmacokinetics similar to that of intravenous administration, but with decreased systemic side effects and increased rectal tissue drug concentration. 14 19 Some animal studies demonstrated that administration of 5FU emulsion in the rectal mucous improved drug accumulation in regional lymph nodes, suggesting that 5FU emulsion therapy might be of potential in treating lymph node metastasis from rectal cancer. 20 , 21 However, the solid form, ie, suppositories, was confined to limited drug contact area with the lesion and poor drug permeability crossing rectal mucous membrane.…”
Section: Introductionmentioning
confidence: 99%
“… 12 , 13 Numerous studies have shown that the colon suppository administration of 5FU appeared to be efficient and showed pharmacokinetics similar to that of intravenous administration, but with decreased systemic side effects and increased rectal tissue drug concentration. 14 19 Some animal studies demonstrated that administration of 5FU emulsion in the rectal mucous improved drug accumulation in regional lymph nodes, suggesting that 5FU emulsion therapy might be of potential in treating lymph node metastasis from rectal cancer. 20 , 21 However, the solid form, ie, suppositories, was confined to limited drug contact area with the lesion and poor drug permeability crossing rectal mucous membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of neoplastic diseases should be aimed at restoring the protective functions of the immune system, and not just at combating the cancer cells themselves. Otherwise, relapse of tumor diseases is inevitable even after the seemingly "successful" treatment [14] .…”
Section: Discussionmentioning
confidence: 99%
“…The dose of 5-FU was selected based on the previous other studies. 6,7) In the case of subcutaneous tumors, mice were first administered with 5-FU either orally or via rectal suppository when tumor volume reached about 200 mm 3 , and thereafter every 3rd day. Glutamic Oxaloacetic Transaminase/Glutamic Pyruvic Transaminase (GOT/GPT) Assay GOT/GPT levels were measured by using a Serum Transaminase assay kit (Asan Pharm, Seoul, Korea) which is based on the Reitman-Frankel method.…”
Section: Dissolution Testmentioning
confidence: 99%
“…7) A conventional rectal suppository such as a suppository formulated with a polyethylene glycol base, which may soften or melt slowly in the site of application due to its relatively high melting point, cannot be rapidly absorbed in the mucous membranes of the absorption site. 8,9) Furthermore, conventional suppositories, which may reach to the end of the canal of the application site, because of its poor mucoadhesive properties, lose drugs at that level, and may also allow the carried drugs to undergo the first-pass effect.…”
mentioning
confidence: 99%